Pattern of Morbidity and Mortality due to Road Traffic Accident at College of Medical Sciences, Chitwan, Nepal - Pohrel, Ava Upadhyay; Acharya, A.; Yadav, A. (Journal of BP Koirala Institute of Health Sciences, 2018)
Background: Road traffic accident (RTA) which is recognized as a public health problem is one of the fastest growing epidemics in the South-East Asian Region. Every hour, 40 people in the region die as a result of collision. Objectives: To estimate the morbidity and mortality of RTA victims and also to assess the pattern of the RTAs at College of Medical Sciences Teaching Hospital, Bharatpur, Chitwan. Methods: This was a cross-sectional study including 100 RTA victims who attended College of Medical Sciences Teaching Hospital, Bharatpur during 2013. Results: Majority of RTA victims were male (76%) and in the age group between 20 and 39 years (48%). Maximum numbers of accidents occurred between 12 noon to 12 midnight (79%). More accident occurred on Friday (23%). Most of the RTAs occurred on motor bike (42.0%) and the most common nature of accident was through collision of the vehicle and fall/slide of moving vehicle (56.0%). Abrasion was the most common injury occurred during the RTA (91%). Almost two-thirds of the victims had laceration, nearly half had swelling and 26% had fractures. Four percentages of victims had fatality. Bad condition of road (37.0%) and speedy driving (23.0%) were the leading causes of RTA. There were 15.0% of victims who were under the influence of alcohol in RTA. Conclusion: There was high number of male victims with motorbike as the major contributor. Abrasion, laceration and fatality were found. Bad condition of road, speed driving and alcohol habit during driving were found to be the leading causes of RTA.